Regional Innovation Model as an Acceleration Strategy Economic Growth in Blitar City - Tris Kamila Rosida; Farida Rahmawati (Budapest International Research and Critics University, 2022)
The Digital Economy has been established as a development strategy for Blitar City in 2021-2026 in the future. This is also supported by the desire to advance competitiveness in the economic sector as stated in the theme of the development of the City of Blitar in 2020, namely